RAGAMAN GENETIK GEN POLIMERASE VIRUS HEPATITIS B PADA PASIEN HEPATITIS B KRONIK DENGAN PENGOBATAN TELBIVUDIN - Gondo Mastutik; Juniastuti Juniastuti; Ali Rohman; Mochamad Amin; Poernomo Boedi Setiawan (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Infection caused by hepatitis B virus (HBV) is still a major global health problem and can cause liver cirrhosis and hepatocellularcarcinoma as well. Telbivudine is one among the drugs used to treat the disease routinely. However, using this drug in a long term therapymight cause mutations in HBV polymerase gene that decreases the effectiveness of the therapy. Here with the researchers report the geneticvariations of the gene isolated from telbivudine-which is used treated chronic hepatitis B patients in Surabaya, Indonesia. The blood serawere collected at Dr. Soetomo hospital from 10 telbivudine-treated and 10 untreated chronic hepatitis B patients. The DNA viral wasisolated and purified from each serum. Sequence polymerase gene at nucleotides 455 to 796 was amplified by PCR, and then analyzedbio informatically to determine their mutation profile. This study revealed a point mutation in HBV25 sample at nucleotide A1525G thatgives rise to I509V modification. Such mutation is also observed in a sequence that is available in Gen Bank with an accession numberAY641562. Additionally, the researchers found point mutations A1554G, T1593C, and C1629T in HBV25 sample and a point mutationA1554G in HBV20 sample. However, these mutations are silent. To conclude, the mutation in HBV polymerase gene among telbivudinetreatedchronic hepatitis B patients in Surabaya is known as A1525G.